Pharmacokinetics of a novel extended half‐life glycoPEGylated factor IX, nonacog beta pegol (N9‐GP) in previously treated patients with haemophilia B: results from two phase 3 clinical trials. Issue 4 (24th February 2017) - Tiede, A.; Abdul‐Karim, F.; Carcao, M.; Persson, P.; Clausen, W. H. O.; Kearney, S.; Matsushita, T.; Negrier, C.; Oldenburg, J.; Santagostino, E.; Young, G.
Abstract : Introduction: Nonacog beta pegol (N9‐GP) is a glycoPEGylated recombinant factor IX (FIX) with an extended half‐life developed for routine prophylaxis and the prevention and treatment of bleeding episodes in patients with haemophilia B. Aim: The aim of this study was to evaluate the pharmacokinetics (PK) of N9‐GP. Methods: Data from 41 previously treated haemophilia B patients, enrolled globally (16 adolescents/adults and 25 children; FIX activity ≤0.02 IU mL −1 ) with no history of FIX inhibitors, were included. N9‐GP was administered once‐weekly as 10 IU kg −1 or 40 IU kg −1 in adolescents/adults and 40 IU kg −1 in children. Blood was sampled up to 168 h (1 week) post dose. Standard PK was estimated on the basis of plasma FIX activity vs. time (PK profiles) using non‐compartmental methods. Furthermore, a population PK analysis and FIX activity predictions were performed. Results: Incremental recoveries were 0.02 (IU mL −1 )/(IU kg −1 ) in both adolescents/adults and children. The extended half‐life resulted in mean trough levels of 0.27 IU mL −1 for adolescents/adults and 0.17 IU mL −1 for children at steady‐state after weekly dosing at 40 IU kg −1 . The population PK analysis confirmed a mono‐exponential decay in FIX activity and allowed for predictions of FIX activity for adolescents/adults above 0.15 IU mL −1 at all times and 6.4 days week −1 in children. Conclusion: N9‐GP has the potential to shift previously treated haemophilia B patients from a severe/moderate disease state into a mild‐ or non‐haemophilic range for most of the dosing interval, which is expected to reduce the number of bleeding episodes.